An Estimate of the Rate of Convergence of the Fourier Series in the Generalized Hölder Metric by Delayed Arithmetic Mean. (7th May 2014) - Nayak, L.; Das, G.; Ray, B. K.
Abstract : We study the rate of convergence problem of the Fourier series by Delayed Arithmetic Mean in the generalized Hölder metric( H p ( w ) ) space which was earlier introduced by Das, Nath, and Ray and obtain a sharper estimate of Jackson's order.